Challenges for communication managers: artificial intelligence and reputation management - Olivos-Farfán, Gabriela (2024)
The present study analyzes the challenges faced by communication managers in strategically managing their clients’ reputations in an environment where artificial intelligence (AI) and Deepfakes are on the rise. A qualitative approach with an ethnographic design is employed. Semi-structured interviews are applied with ten directors of communication agencies in Lima, Peru. For the analysis of results, a thematic analysis was developed to understand in depth their perspectives, strategies and challenges in relation to reputation management in the face of the propagation of AI-generated content. As a result, there is evidence of a lack of planning to address the emerging problem due to the lack of specific cases linked to Deepfakes, which has limited the preparation for possible crises, highlighting the need to anticipate potential scenarios for an effective response. Risks and challenges are identified, highlighting the importance of a solid reputation for clients and the management of a crisis plan.